Income Gains and the Geography of the US Home Ownership Boom, 1940 to 1960 - Collins, William J.,Niemesh, Gregory (National Bureau of Economic Research, 2023)
Income and home ownership both surged in the United States between 1940 and 1960. We use cross-place variation in changes in real income to assess the importance of income gains to the mid-century home ownership boom. OLS and IV estimates suggest that a large share of the overall increase in home ownership was attributable to wage gains that were both large on average and widely spread across workers. This research complements the literatures on how New Deal mortgage market innovations and the World War II and Korean War GI Bills promoted home ownership in this period
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Wohneigentum; Konjunktur; Haushaltseinkommen; Wirtschaftsgeographie; USA; Wage Level and Structure; Wage Differentials; U.S.; Canada: 1913-; Housing Demand